Physical Activity and Health-Related Fitness of Grade 11 Students - Callas, Darlene; Nillos, Charles; Guitche, Melona; Perez, Rexomar (Technium Social Sciences Journal, 2024)
The lockdown period has led to a decline in physical activity and fitness among students with increasingly embraced sedentary behaviour. This study aimed to assess the physical activity (PA) level and health-related fitness (HRF) status of students according to sex and academic strand, also determining whether significant differences existed. The study was conducted in a large public high school responding to the International Physical Activity Questionnaire-Long Form (IPAQ) and the Philippine Physical Fitness Test. The study employed a descriptive-comparative research design and employed stratified random sampling with proportional allocation. The students demonstrated a moderate PA level, regardless of sex and academic strand. Regarding health-related fitness, most students exhibited normal BMI, excellent strength in the basic plank, good cardiovascular endurance in the 3-minute step test, good flexibility in the zipper test, fair flexibility in the sit and reach test, and poor performance in the push-up. Furthermore, significant differences were found in BMI and strength when grouped by sex. In conclusion, most students maintain moderate physical activity, surpassing local restrictions and avoiding sedentary behaviour. Also, most students have shown muscular endurance and flexibility in various tasks but have yet to focus as much on strengthening their arms and core muscles. The FIT-UP YOU program has been developed to address this issue, focusing on improving weight and overall HRF status among young overweight/obese and underweight students.